2015
DOI: 10.1016/j.yrtph.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Is the shape of the decline in risk following quitting smoking similar for squamous cell carcinoma and adenocarcinoma of the lung? A quantitative review using the negative exponential model

Abstract: One possible contributor to the reported rise in the ratio of adenocarcinoma to squamous cell carcinoma of the lung may be differences in the pattern of decline in risk following quitting for the two lung cancer types. Earlier, using data from 85 studies comparing overall lung cancer risks in current smokers, quitters (by time quit) and never smokers, we fitted the negative exponential model, deriving an estimate of 9.93years for the half-life - the time when the excess risk for quitters compared to never smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“… 24 Besides, from view of actual pharmacologic effect, quitting smoking showed different effect among different cell type of pulmonary malignancy. 25 In our study, 55 current smokers were identified. A 75% belongs to adenocarcinoma patients and 25% belongs to nonadenocarcinoma patients.…”
Section: Discussionmentioning
confidence: 98%
“… 24 Besides, from view of actual pharmacologic effect, quitting smoking showed different effect among different cell type of pulmonary malignancy. 25 In our study, 55 current smokers were identified. A 75% belongs to adenocarcinoma patients and 25% belongs to nonadenocarcinoma patients.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the majority of previous studies showed a clear negative association between smoking cessation and lung cancer. Evidence suggests that this association varies by histologic cell type [ 24 , 25 ]. An increased duration of smoking cessation has been linked to a decreased risk of small cell and squamous cell carcinoma but not with adenocarcinoma [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that this association varies by histologic cell type [ 24 , 25 ]. An increased duration of smoking cessation has been linked to a decreased risk of small cell and squamous cell carcinoma but not with adenocarcinoma [ 24 , 25 ]. Apart from the role of histologic cell type in this association, the time that needs to pass before the risk of lung cancer among quitters reaches that of never smokers is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…RRs for ex-smokers were also substantially higher for squamous cell carcinoma (8.74, 95% CI 6.94-11.01) than for adenocarcinoma (2.85, 2.20-3.70). In a separate publication [58], based on data from 85 studies comparing cancer risks in current smokers, quitters (by time quit) and never smokers, it was found that the rate of decline in RR following quitting was somewhat less rapid for adenocarcinoma than for squamous cell carcinoma, where the half-lives were estimated, respectively, as 14.45 (11.92-17.45) and 11.68 (10.22-13.34). The slower decline in risk for adenocarcinoma was evident in subgroups by sex, age and other factors.…”
Section: Variation In Relative Risk Of Lung Cancer By Histological Typementioning
confidence: 99%